PENERTIBAN ANAK JALANAN OLEH DINAS SOSIAL KOTA MEDAN DI KECAMATAN MEDAN SUNGGAL - Hasugian, Esra Endang (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
One of the social phenomena that is currently happening in Indonesia, especially in the city of Medan, is the increasing number of street children. This study aims to find out how the process of controlling street children by the Social Service of Medan City in Medan Sunggal District. This research method is descriptive research with a qualitative approach. Data collection techniques used are observation, interviews, and documentation. The informants in this study were 3 street children, the Medan City Social Service and parents of street children. The results of the study indicate that the process of controlling street children in the city of Medan includes the implementation of raids by the Civil Service Police Unit, the Medan City Social Service, as well as URC Field Workers, and Polresta. After being caught in a raid, the street children will be brought to the Social Service to continue the control phase. Data collection, disclosure and understanding of the problem (assessment) at this stage, the Social Service staff will request and collect information and information on street children caught in raids. After the Social Service carried out the data collection, street children were also asked for information to reveal the cause of the children taking to the streets. The Department of Social Affairs will contact the parents of the street children through the head of the neighborhood or the kelurahan where the street children live. The provision of follow-up actions from the Social Service to street children who were caught by controlling operations were grouped based on the presence of their parents, namely: 1. To street children who have parents, 2. To street children who do not have parents. The results of interviews and observations show that the Medan City Social Service has carried out control operations / raids on street children in Sunggal Medan to reduce social problems caused by street children.